Higher than present global mean sea level recorded by an Early Pliocene intertidal unit in Patagonia (Argentina) - Rovere, Alessio; Pappalardo, Marta; Richiano, Sebastian; Aguirre, Marina; Sandstrom, Michael R.; Hearty, Paul J.; Austermann, Jacqueline; Castellanos, Ignacio; Raymo, Maureen E. (Communications Earth & Environment, 2020)
Reconstructions of global mean sea level from earlier warm periods in Earth’s history can help constrain future projections of sea level rise. Here we report on the sedimentology and age of a geological unit in central Patagonia, Argentina, that we dated to the Early Pliocene (4.69–5.23 Ma, 2σ) with strontium isotope stratigraphy. The unit was interpreted as representative of an intertidal environment, and its elevation was measured with differential GPS at ca. 36 m above present-day sea level. Considering modern tidal ranges, it was possible to constrain paleo relative sea level within ±2.7 m (1σ). We use glacial isostatic adjustment models and estimates of vertical land movement to calculate that, when the Camarones intertidal sequence was deposited, global mean sea level was 28.4 ± 11.7 m (1σ) above present. This estimate matches those derived from analogous Early Pliocene sea level proxies in the Mediterranean Sea and South Africa. Evidence from these three locations indicates that Early Pliocene sea level may have exceeded 20m above its present level. Such high global mean sea level values imply an ice-free Greenland, a significant melting of West Antarctica, and a contribution of marine-based sectors of East Antarctica to global mean sea level.